Pragmatisme Charles S. Peirce dan Implikasinya Pada Penentuan Awal Waktu Salat dan Pelaksanaannya - Arjuna Hiqmah Lubis (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
Philosophers through their philosophy continue to provide ideas in defining something that is in accordance with each. Charles Sanders Peirce with his school of philosophy Pragmatism. Peirce is an expert in various fields of science such as mathematics, chemistry, geodesy. Then this fantasy genre of pragmatism attracted many Americans and also in various parts of Europe through his friend William James. Flow Pragmatism